Activities of the wintering party of the 25TH Japanese Antarctic Research Expedition in 1984-1985 - Takeo Hirasawa (National Institute of Polar Research, 1986)
The 25th wintering party of the Japanese Antarctic Research Expedition (1984-1985) consisting of thirty-five members was in charge of research activities around Syowa and Mizuho Stations for the period from February 1984 to January 1985. The main programmes of the research works were the sounding rocket experiments for auroral studies, the inland traverse for the glaciological and meteorological studies and the coastal traverse for the biological and glaciological studies. The inland traverse party made a 126-day trip from 4 Octorber 1984 to 6 February 1985 covering about 3000km in East Queen Maud Land. The main object was to reach the second highest dome of the Antarctic ice sheet around 77°S and 35°E. However, the traverse was suspended at 75°S and 35°E because the medical doctor of the traverse party was asked urgently to go back to Syowa Station for the medical treatment of a wounded person there. The ice core drilling at Mizuho Station attained a depth of 700.6m and in situ observation was made intensively on the obtained core samples. The coastal party travesed more than 1000km on the sea ice around the southeastern part of Lutzow-Holm Bay. The studies of biological processes in the coastal ecosystem were carried out in conjunction with the international BIOMASS programme. Three S-310JA type rockets were fired off at Syowa Station. Objects of measurements were auroral particles, electron densities, magnetic fields and auroral images in aurora. Through the successful rocket flights, significant information to reveal the physical nature of auroras was obtained.